Virtual Relationships: Short- and Long-run Evidence from BitCoin and Altcoin Markets - Pavel Ciaian; d'Artis Kancs; Miroslava Rajcaniova (Publications Office of the European Union, 2017)
This study empirically examines interdependencies between BitCoin and altcoin markets in the short- and long-run. We apply time-series analytical mechanisms to daily data of 17 virtual currencies (BitCoin + 16 alternative virtual currencies) and two Altcoin price indices for the period 2013-2016. Our empirical findings confirm that indeed BitCoin and Altcoin markets are interdependent. The BitCoin-Altcoin price relationship is significantly stronger in the short-run than in the long-run. We cannot fully confirm the hypothesis that the BitCoin price relationship is stronger with those Altcoins that are more similar in their price formation mechanism to BitCoin. In the long-run, macro-financial indicators determine the altcoin price formation to a greater degree than BitCoin does. The virtual currency supply is exogenous and therefore plays only a limited role in the price formation.
Keywords: E31; E42; G12; 330; BitCoin; altcoins; virtual currencies; price formation; supply; demand; macroeconomic development